Levels of depression, anxiety, and stress among emerging adults in the Philippines: an exploratory spatial analysis. - Regencia, Zypher Jude G; Marteja Jr., Vergel T; Baja, Emmanuel S (Journal of Public Health, 2025)
Background Despite the enactment of the mental health law, mental illness in the Philippines is the third most prevalent form of morbidity; hence, screening is warranted, especially among Filipino emerging adults. This exploratory spatial analysis study aimed to identify spatial clusters of depression, anxiety, and stress among Filipino emerging adults. Methods A convenience sampling online self-administered survey was used to collect data from 18 to 29 Filipinos (n = 2729) in the Philippines. The Depression Anxiety Stress Scales–21 was utilized to ascertain the participant's level of depression, anxiety, and stress. Coordinates were plotted with administrative boundaries and OpenStreetMap layer using the software ArcGIS, and clusters were evaluated using the Mapping Clusters—Hot Spot Analysis and Spatial Autocorrelation (Moran's I). Results Results of mapping clusters regarding age group and sex showed that Pangasinan, Nueva Ecija, Tarlac, Pampanga, Bulacan, Rizal, Laguna, Cavite, and the National Capital Region in Luzon Island are considered hotspots for severe and extreme levels of depression, anxiety, and stress. These conditions were most prevalent among early emerging adults and females. Conclusion Our study provided spatial locations of populations susceptible to mental health disorders, and these preliminary findings have implications for health policy and program expansion for mental health.